If it's not what You are looking for type in the equation solver your own equation and let us solve it.
720=(2x-6)(x-6)
We move all terms to the left:
720-((2x-6)(x-6))=0
We multiply parentheses ..
-((+2x^2-12x-6x+36))+720=0
We calculate terms in parentheses: -((+2x^2-12x-6x+36)), so:We get rid of parentheses
(+2x^2-12x-6x+36)
We get rid of parentheses
2x^2-12x-6x+36
We add all the numbers together, and all the variables
2x^2-18x+36
Back to the equation:
-(2x^2-18x+36)
-2x^2+18x-36+720=0
We add all the numbers together, and all the variables
-2x^2+18x+684=0
a = -2; b = 18; c = +684;
Δ = b2-4ac
Δ = 182-4·(-2)·684
Δ = 5796
The delta value is higher than zero, so the equation has two solutions
We use following formulas to calculate our solutions:$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}$$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}$
The end solution:
$\sqrt{\Delta}=\sqrt{5796}=\sqrt{36*161}=\sqrt{36}*\sqrt{161}=6\sqrt{161}$$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}=\frac{-(18)-6\sqrt{161}}{2*-2}=\frac{-18-6\sqrt{161}}{-4} $$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}=\frac{-(18)+6\sqrt{161}}{2*-2}=\frac{-18+6\sqrt{161}}{-4} $
| -11=-6+k | | X^2-7x+12=4x-4 | | 16t+3t+4t-20t-2t=14 | | 18-2q=20 | | 1=k2 | | 4t^2−2t+19=0 | | 5=-4-y-21 | | 4t^2-2t+19=0 | | 4s-2s+s=9 | | 3(2y+3y)=135 | | 20x+30=3x+27 | | 6=-3/5+u | | 5-6k=4-7 | | V+5v+v-6v=7 | | -7=u-5 | | 6q-15q+-4q-8q+16q=-15 | | 2s=-24 | | 16r-6r=-20 | | 20a+4a-16a-7a=17 | | 3t2=t+6 | | 7y+13y+12y=16 | | 2/5x-5/7x=5/3+4/x | | 3/2m=112 | | 8n-9=-3 | | 8h-5h-h=18 | | X(2x-3)=252 | | 5/8p=90 | | -5(x+2)+2x+6=6x+6 | | 5q+2=-13 | | 5x+x-2+69=180 | | 2/3x-16=3/5x-14 | | 14w-9w-w-w-2=8 |